Evaluating the Dynamic Accessibility of Metro Systems in Overcrowded Conditions. Issue 11 (November 2020) - Li, Wei; Luo, Qin; Zephaniah, Samwel; Liu, Zhaoran
Metro accessibility is a concept used to describe the dynamic accessibility index of metro transportation systems. Most studies on accessibility apply a static approach, which overlooks the index fluctuations throughout the day. While it is possible to represent the accessibility using a single index, the ability to capture the dynamic nature of the index is important in understanding the quality of a transportation service and identify actionable aspects for improvement. For example, when the metro system is overcrowded and passengers fail to board the next arriving train, they instead wait for the subsequent train. As a result, the accessibility of the system is deemed to be lower than when its condition is uncrowded. This paper analyzes and integrates two aspects of metro accessibility: the performance of metro networks; and the dynamics of train schedules. An evaluation model in the form of a gravity model is proposed to measure the accessibility between each pair of stations with the dynamic travel time. This allows us to obtain profiles that highlight the daily variations in accessibility in the metro network and to identify the influence of congestion among stations. The effectiveness of the proposed evaluation model is validated using the metro network of Shenzhen in China. Results show that the proposed methodology provides useful information for passengers and travel guides as well as technical reference for the metro operation guidelines that are used to compile train schedules.